MANAGEMENT OF SPINAL GUNSHOT WOUND INJURIES - KULCHESKI,ÁLYNSON LAROCCA (2021)
ABSTRACT Objectives Elaborate a care protocol for spinal gunshot wounds (GSWs), based on the experience of more than fifteen years of treating this type of injury. Methods A retrospective cross-sectional analysis of the electronic medical record data of a tertiary hospital related to the treatment of spinal GSWs between January 2002 and January 2018. Results The management proposed was applied to 700 patients. Epidemiological data collected describes the population served. Conclusions An easy-to-use treatment flowchart was developed that, according to factors related to the neurological condition, projectile location, lesion stability and additional criteria, allows the objective determination of the best treatment option for each case. Level of evidence II; Retrospective Study.